Shakleebyzulfi / Zulfi Aizuddin Zainuddin - Zainuddin, Zulfi Aizuddin (2021)
Shaklee is a brand name for both my product and my business. My company's mission is to provide our customers with a healthy and enjoyable way of life. We aspire to be the greatest supplement company in Malaysia. My company began operations on April 15, 2020. The intended audience consists of students and adults between the ages of 20 and 30. We wish to provide our customers a lower price and better service than any other Supplement Company.